Incidence of aphid-transmitted viruses in raspberry and raspberry aphids in Norway and experiments on aphid transmission of black raspberry necrosis virus - Sapkota, Bijaya; Trandem, Nina; Fránová, Jana; Koloniuk, Igor; Blystad, Dag-Ragnar; Hamborg, Zhibo (Frontiers in Plant Science, 2024)
Raspberry (Rubus idaeus L.) is susceptible to aphid-borne viruses. We studied the incidence of four of them -black raspberry necrosis virus (BRNV), raspberry leaf mottle virus (RLMV), raspberry vein chlorosis virus (RVCV), and Rubus yellow net virus (RYNV) -in raspberry plants and aphids in and around Norwegian raspberry crops for three years (2019, 2021, and 2022). Most of the samples were from symptomatic plants. Applying RT-PCR, 274 leaf samples and 107 aphid samples were analyzed. All four viruses were found, but BRNV dominated: it was detected in 93% of the 178 leaf samples with virus and was the only virus that occurred more frequently as a single infection than in coinfections with the other viruses. The old cv. Veten had the highest virus incidence (97%) among the sampled plants, followed by uncultivated raspberry in the boundary vegetation (82%). All aphids identified were Amphorophora idaei and Aphis idaei. BRNV and/or RLMV was detected in 27% of the aphid samples. Notably, BRNV was detected in 30% of A. idaei samples, a species not known as a BRNV vector. In subsequent transmission experiments we found that although A. idaei can acquire BRNV within one hour, it did not transmit the virus to healthy raspberry plants. In contrast, Am. idaei, a known BRNV vector, was able to acquire the virus within one minute and transmit it within one hour of inoculation. Our study will improve the identification and management of BRNV.